Co-Designing Fashion with AI in the Phygital Scenario - Paolo Franzo; Elisabetta Cianfanelli; Andrea Quartu (Convergências - Revista de Investigação e Ensino das Artes)
The fashion industry has been grappling with exponential technological and digital transformation for several years now, revolutionizing the way ideas are conceived, designed, produced, communicated, and sold. Artificial Intelligence, integrated across Fashion Design, gives rise to new scenarios and acts of cultural and social construction in which human creativity and technology merge into new co-creative and collaborative approaches. This contribution aims to investigate the methodologies and practices through which this emerging phenomenon alters the fashion design process and the skills of the professionals involved. The analyzed case studies help to understand the ways in which datasets are constructed and processed, starting from archives, and the process of collaboration between humans and technology in fashion design.